A revision of Lanonia (Arecaceae, Coryphoideae, Livistoninae) - Henderson, Andrew; Dựng, Nguyễn Quốc (Phytotaxa, 2022)
A revision of Lanonia was carried out based on morphological data. Two hundred and eighteen herbarium specimens were examined and scored for 30 quantitative and 24 qualitative variables. Application of the Phylogenetic Species Concept to 13 preliminary species of Lanonia resulted in recognition of 19 phylogenetic species. Of these, six are recognized as new (L. honbaensis, L. honheoensis, L. kontumensis, L. montana, L. nuichuaensis, L. tenuisecta). Nomenclature, descriptions, and distribution maps are provided for all species. Images of the type specimens of all new species are provided as well as images of most qualitative variables.